An Investigation of How Chinese University Students Use Social Software for Learning Purposes. (13th May 2015) - Zhang, Zuochen; Xue, Ying
Abstract: Social software (also called "social networking sites" or "social media sites") is used by people of all walks of life around the globe, and a variety of research studies have been conducted regarding its use for learning purposes, as the pedagogical value of the informal communication space has been recognized by researchers with different perspectives. Facebook and Twitter, which are very popular social software in many countries, are not available to general users in mainland China, where alternatives, e.g., QQ and WeChat are widely used. This paper reports findings of a study that investigated how students from three Chinese universities of different geographic locations (one from Northeast China, one from Northwest China, and another from Southwest China) use the social software for learning purposes. Data were collected from interviews with some of the users, and observation of how the spaces were used, in the past two years. Based on a review of relevant literature and the analysis of the research data, the authors' reflections and recommendations are presented with the hope to offer educators of higher education some useful reference to consider when they design curriculum and courses that could provide students with an enriched learning experience.